Dynamic Compaction Vibration Monitoring in a Saturated Site - Hamidi, Babak; Nikraz, Hamid; Varaksin, S. (Australian Geomechanics Society, 2011)
Dynamic Compaction is a well established ground improvement technique in which a heavy pounder is dropped from a significant height to improve the soil’s mechanical properties. The pounder impact creates waves that compact the soil; however these waves may also be a nuisance to and damage neighbouring structures and facilities. Peak particle velocity (PPV) has been identified as the most suitable parameter for assessing vibration associated risks. Previous researchers have proposed a number different equations for predicting PPV. Dynamic Compaction has recently been used for soil improvement in Oman’s Blue City Project. Particle velocities and vibration frequencies in three directions have been monitored at several distances during the different phases of ground treatment. In all phases PPV has been recorded to be in the radial direction. It has been observed that although it appears that vibration frequency is not influenced by the deep compaction phase, does increase with the progression of work and application of later phases of Dynamic Compaction. This increase is more pronounced at farther distances, but becomes negligible when impact point is closer than a critical distance.